O Moderno Na Iluminação Elétrica Em Berlim Nos Anos 1920 - Varolli, Renan De Andrade [UNIFESP] (2017)
This thesis analyzes electric lighting in Berlin in 1920’s. The work starts from industrially produced objects for usufruct and circulation among the masses, such as buildings, advertising pieces and films, with the aim of understanding modernity’s features on this metropolis then. In the course of the text, it is approached as well tensions and connections between art and industry, relations that some times accompanied modern, modernism and modernization, correlative concepts of modernity. Having a background of contrasts and contradictions in Germany’s capital during the period of its history known as Weimar Republic (1919-1923), it is attempted to draw how theoretical-historiographic reappraisal of artistics and cultural programs regarded as decadent could be succeeded by technological progress.